THE EXISTENCE OF THE LAUJE TRIBE IN FACING SOCIAL CHANGE IN TINOMBO VILLAGE, TINOMBO SUB-DISTRICT, PARIGI MOUTONG DISTRICT - Yuliatmi, Yuliatmi; Tubagus, Najwa; Aprilia, Anggi; Mokodompit, Prawira (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
This research explores the existence of the Lauje tribe in Tinombo Village, Tinombo Sub-district, Parigi Moutong Regency, in the context of social change. The Lauje tribe, which is divided into urban and rural groups, is known as a primitive tribe that still maintains ancestral traditions and culture even though it has begun to interact with outside communities and recognize technology. Using descriptive qualitative methods, this research examines the early life of the Lauje before and after social change, as well as their adaptation strategies. The tribe has a unique language and beliefs, and despite embracing Islam and Christianity, they still retain some elements of their old beliefs. Social change in Lauje society is influenced by both internal and external factors, including the expectation of progress and external cultural influences. Despite progress in the adoption of modern technology and interaction with outside society, some parts of the tribe still retain old traditions, including animist religions.